Effect of feeding graded levels of broken rice on blood biochemical profile of White Pekin ducks during second Year of laying - Naik, P. K. (Indian Journal of Animal Nutrition, 2020)
A study was conducted to find out the effect of feeding graded levels of broken rice (BR) replacing wheat in the diet of White pekin ducks on blood biochemical profile during second year of laying. White pekin laying ducks (75; 82 weeks) were divided into five groups; and diets without (BR-0) and with BR, replacing 25 (BR-25), 50 (BR-50), 75 (BR-75) and 100 (BR-100), percent wheat; were fed for a period of 73 days. The blood glucose (mg/dl) level ranged from 171.23 to 182.07 among the groups; however it was non-significantly (P>0.05) higher in BR-50 than the other groups. The serum total protein and globulin levels (g/dl) were higher (P<0.05) in BR-50 group than BR-100 group; however, the serum total protein and globulin levels in ducks fed BR were similar with the control. The serum albumen content (3.59-3.65, g/dl) was similar (P>0.05) among the groups. The serum triglycerides content (mg/dl) ranged from 294.10 to 297.70 and was similar (P>0.05) among the groups. There was no effect of BR on the serum cholesterol content (130.81-147.60, mg/dl) of the ducks. The uric acid content (8.07-8.30, mg/dl) was similar among the groups. The Ca (10.17-10.49, mg/dl) and P (3.73-4.08, mg/dl) contents of the serum were also comparable (P>0.05) among the groups. It can be concluded that the complete replacement of wheat by broken rice in the diets of white Pekin laying ducks during second year of egg production had no affect on the blood biochemical profile of White Pekin ducks.Â